TRAINING OF BILHIKMAH QURAN READING METHOD FOR ISLAMIC PRIMARY TEACHERS - Supriadi, Udin; Anwar, Saepul; Romli, Usup (Universitas Pendidikan Indonesia, 2020)
Abstract. Every Muslim is encouraged to be able to read Quran. Therefore, it become the main purpose on the conduction of Islamic education, starting from primary level. Realistically, only 30% students were able to meet the objective. One of the factors is due to the inappropriate learning method being used. In this case, Bilhikmah is introduced as a method to learn Quran shortly which has been effectively proved. The training aimed to provide the Islamic primary teachers with adequate knowledge of Bilhikmah method. The considered target in this study is 75% from 40 teachers would be able to implement Bilhikmah method. However, the training involved various methods such as presentation performance, question and asking session, practice, as well as small group and individual mentorship. The result shows that all participated target (100%) succeed to comprehend the three volumes of Bilhikmah book, while practical tajweed book is mastered by 75% participants. Furthermore, the training participants are then applied Bilhikmah method on Quran learning process in their own schools.Abstrak. Setiap Muslim dituntut untuk bisa membaca Al-Quran. Karena itu salah satu tujuan Pendidikan Agama Islam (PAI) di Sekolah Dasar agar para bisa membaca Al-Quran. Realitasnya hanya sekitar 30% siswa yang berhasil meraih tujuan pendidikan ini. Salah satu penyebabnya, keliru menerapkan metode pembelajaran. Bilhikmah merupakan metode cepat membaca Al-Quran yang terbukti efektif. Kegiatan pelatihan ini bertujuan membekalkan metode Bilhikmah kepada para guru PAI SD. Targetnya 75% dari 40 GURU mampu mengimplementasikan metode Bilhikmah. Pelatihan menggunakan beragam metode, yakni: presentasi, tanya-jawab, demonstrasi, praktek, bimbingan kelompok kecil, dan bimbingan individual. Hasil pelatihan hampir seluruh peserta (100%) berhasil menguasai buku Bilhikmah 1, 2, dan 3, sedangkan buku tajwid praktis dikuasai oleh 75% peserta. Mereka pun kemudian mengimplementasikan metode Bilhikmah dalam pengajaran membaca Al-Quran di sekolah masing-masing.